Studying the algorithm for controlling the generator set of a mining dump truck using simulation models - Muraviev, A. S.; Pirozhkov, R. D.; Buzunov, N. V.; Kartashov, A. B.; Dubinkin, D. M.; Efremenkov, A. B. (AIP conference proceedings, 2022)
The work describes control algorithms for a generator set, which is a part of a combined power plant, made according to a series circuit for a 6x6 mining dump truck. The general approaches used in developing control systems for such generator sets are described. The testing methods and simulation mathematical models used to analyze the operation of control systems for generating sets are presented. As an example, the architecture of the developed control system used on a mining dump truck is given. The developed control system and simulation model allow us to analyze the generator set and energy storage behaviour, at various loads on the traction electric motor.